Effect of tannic acid on corrosion behavior of carbon steel in NaCl solution. Issue 1 (January 2019) - Xu, Wenhua; Han, En-Hou; Wang, Zhenyu
Abstract: Corrosion behavior of unrusted Q235 carbon steel was investigated in 3.5% NaCl solutions with 1–5 wt% tannic acid addition, using electrochemical methods including electrochemical impedance spectra (EIS), potentiodynamic polarization and scanning vibrating electrode technique (SVET) combined with surface analysis. Results show that the corrosion rate decreases with increasing tannic acid concentration. As compared with tannic acid-free solution, 1% tannic acid does not provide inhibition effect during the whole immersion, while inhibition effect is observed for 3% tannic acid after 8 h and for 5% tannic acid after 4 h. The inhibition efficiency by weight loss measurements ( η w ) for 1%, 3%, and 5% tannic is around −17.2%, 40.3%, and 51.5%, respectively. Corrosion of unrusted carbon steel in the presence of tannic acid is attributed to the joint effect of tannic acid adsorption and pH decrease. Formation of ferric-tannates is verified by X-ray photoelectron spectroscopy (XPS) and Raman spectra. The reaction mechanism between tannic acid and unrusted carbon steel is proposed.